Contagious order as a risk factor for liver fibrosis progression in co-infection with human immunodeficiency virus, hepatitis B and C viruses - E. P. Feoktistova; D. Yu. Konstantinov; E. S. Malova; I. P. Balmasova (Журнал инфектологии, 2024)
In triple co-infection with HIV/HCV/HBV, the prognosis is significantly poorer and life expectancy is lower because of the rapid progression of liver fibrosis or development of hepatocellular carcinoma. The aim of this study was to test the hypothesis that one of the risk factors for the unfavorable course of HIV/HCV/HBV co-infection is contagious order and the interval between coinfections. The study analyzed anamnestic data and the results of direct follow-up of 97 patients co-infected with HIV/HCV/HBV for 1-2 years. Patients were divided into three study groups: (1) HIV as the first pathogen, (2) HCV as the first pathogen, and (3) HBV as the first pathogen. For each patient, the period (in years) between the acquisition of the first and subsequent pathogens was considered. During the fol-low-up period, viral HIV, HCV, and HBV load was assessed by PCR, and annual transient liver fibro-elastometry was performed to determine the fibrosis stage using the METAVIR scoring system. The risk of progressive liver fibrosis in HIV/HCV/HBV co-infection is higher when HIV or HBV is the first pathogen, but the interval between the acquisition of HBV and other viruses is 10 years. Meanwhile, a stable course of liver fibrosis is associated with an HBV viral load of >7,200 copies/ml. In the risk group, the most effective antiretroviral therapy was a combination of reverse transcriptase inhibitors, HIV protease inhibitors, and direct antiviral (anti-HCV) drugs. Therefore, the order of infection and intervals between pathogen acquisition in triple co-infection with HIV/HCV/HBV have a significant effect on liver fibrosis progression, which requires specific approaches to the organization of diagnostic tests and the control of antiretroviral therapy.